SWOT Analysis for Marketing Strategies of Fajar Margiyono's Bag and Luggage Business in Surakarta - Musa Fatahilah Fajar; Muhammad Sholahuddin (Universitas KH. Abdul Chalim Mojokerto, 2025)
A marketing strategy is an integrated plan that guides businesses in achieving their marketing objectives. Fajar Margiyono Bags and Luggage, a small and medium enterprise (SME) established in Surakarta in 1990, faced intense competition and internal challenges following the owner's departure. This study aims to formulate an effective marketing strategy using SWOT analysis through a qualitative approach involving field studies with data collected via observation, interviews, and documentation. The findings indicate that the most appropriate strategy is the WO (Weaknesses-Opportunities) strategy, leveraging external opportunities to address internal weaknesses. Product innovation includes introducing eco-friendly and multifunctional luggage designs tailored to specific customer segments, such as travelers and professionals. Adopting digital technology entails creating an e-commerce platform, enhancing social media marketing, and utilizing customer relationship management (CRM) software to improve customer interactions. Strengthening distribution networks involves establishing partnerships with online marketplaces and exploring direct-to-customer (DTC) models through a robust website. The study also examines external threats such as economic downturns, market saturation, and rising raw material costs, recommending mitigation strategies like cost management, supplier diversification, and market trend analysis. An implementation roadmap includes short-term goals like launching new product lines and social media campaigns, mid-term goals like integrating CRM software and expanding distribution networks, and long-term goals like building a sustainable supply chain and investing in advanced digital marketing tools. By addressing internal weaknesses, mitigating external threats, and seizing market opportunities, this study contributes to the development of practical marketing strategies for SMEs, enabling improved competitiveness and sustainable growth.